Revision of the scale worms (Polychaeta:Aphroditoidea) occurring in the seas surrounding the Arabian Peninsula. Part I: Polynoidae - Wehe, Thomas. (Fauna of Arabia, 2006)
The study presented here is the first in a series on the scale worms of the seas surrounding the Arabian Peninsula: Suez Canal, Red Sea, Gulf of Aden, Arabian Sea, Gulf of Oman, The Gulf. Based on type specimens and additional published and unpublished specimens, this is the first revision of the Polynoidae that are currently recognised from this area. Detailed descriptions and figures are provided as well as identification keys to all taxa, and taxonomic problems are discussed. Discussions of the distribution, faunal affinities, Lessepsian migration and endemism are given in a zoogeographic account. The occurrence of 44 species belonging to 23 genera and seven subfamilies is confirmed. Twenty-three species represent new records for one or more of the respective seas. Four new species are described: Harmothoe marerubrum n. sp., Lepidonotus polae n. sp., Parahalosydnopsis arabica n. sp., Pararctonoella marginopapillata n. sp.; and Uncopolynoinae n. subf. is introduced. Harmothoe grisea, Lepidasthenia nuda and Lepidonotus impatiens are redescribed. Bouchiria, Iphione reticulata, Lepidonotus impatiens meridionalis and L. australiensis [type locality red sea] are considered junior synonyms. Harmothoe vesicudenta is transferred to the genus Malmgreniella. The diagnoses of 10 genera are emended. The fauna documented is closely related to that of the Indo-West Pacific with at least 30 species out of 44 in common. Two species are likely to represent Lessepsian and two Anti-Lessepsian migrants. For the present, 10 species (23 %) are considered endemic to the area.
World Polychaeta Database (WPolyDb)